INDUCED DRAFT FAN DOMINANT FREQUENCY DETECTION USING SHORT-TIME FOURIER TRANSFORM METHOD - Dedik Romahadi; Wiwit Suprihatiningsih; Gian Villany Golwa; Mahesh Kumar (Jurnal Rekayasa Mesin, 2023)
Weak suction and large vibrations indicate an Induced Draft Fan (IDF) problem. The Fast Fourier Transform (FFT) method cannot be applied to non-stationary vibration signals. Therefore, this study aims to analyze non-stationary vibration signals for IDF vibration signals at start-up so that the source of damage to the IDF can be found. The research process begins with a brief measurement of both bearing locations with horizontal and axial axes. Processing of the vibration signal from the measurement using the FFT method and the Short Time Fourier Transform (STFT). Based on the STFT spectrogram graph for measurements on the horizontal and axial axes, the dominant frequency values are the same. The frequency with the largest amplitude value is at one RPM IDF or 25 Hz. High vibration at 1 RPM is a big indication that the IDF is experiencing unbalance.